Ultrasound-assisted extraction of carotenoids from mango (Mangifera indica L.‘Ataulfo’) by-products on in vitro bioaccessibility - Sáyago-Ayerdi, Sonia G. (2018)
Mango by-products (peel and paste) are a source of carotenoids, but their bioaccessibility (BA) can be limited by dietary fiber (DF), since it retains these compounds within its structure. The aim of this study was to evaluate the influence of ultrasound-assisted extraction (UAE) on the BA of carotenoids by an in vitro digestion model. The β-cryptoxanthin (βCr) content (3.59 ± 0.43 mg/g DW) in UAE-peel was higher than that in Control-peel (0.66 ± 0.03 mg/g DW). The β-carotene (βC) content in UAE-peel and UAE-paste was higher than that in Control-peel and Control-paste. The %BA in the UAE-peel improved by 46.93%, 35.21% and 32.62% for βCr, Lutein (Lut), and βC, respectively, compared to that in the Control-peel, and in the UAE-paste, the treatment improved the %BA for Lut, βCr, and βC by 46.04%, 44.16%, and 44.01% respectively, compared with that of the Control-paste. A high percentage of non-bioaccessible βC was shown for the Control-peel (79.48%) and Control-paste (70.41%), and the percentage was lower in the UAE samples. The released carotenoids were quantified in a kinetic model, and β-Cr, Lut, and βC were effectively released in mango UAE-peel. The constant release rate, k, did not show significant differences in both samples. A 2-parameter non-linear regression model was the best fit for the release kinetics. The use of UAE on in vitro digestion conditions noticeably improved the bioaccessibility of carotenoids in mango by-products.